Pengaruh Model Pembelajaran Market Place Activity Or Sales Promoting Activity Creative Terhadap Minat Belajar PAI Di SMA Negeri 3 Kota Pasuruan - Lailiyah, Aini Maftukhatul (Al-Makrifat: jurnal kajian Islam, 2020)
This research is motivated by the phenomenon of students’ interest in learning. Where students need support from the learning model. Because with the existence of a creative and innovative learning model, students are able to be more active, creative, able to increase literacy in their learning, and be able to work together between friends, the students’ interest in learning will increase. And the learning model can be applied to one of the subjects of Islamic Religious Education. The objectives of this study were (1) to determine the learning model of Market Place Activity or Sales Promoting Creative Activity in SMA Negeri 3 Pasuruan, (2) to determine the students’ interest in learning Islamic religious education at SMA Negeri 3 Pasuruan City and (3) to determine how much the influence of the Market Place Activity or Sales Promoting Creative Activity Learning model on students’ interest in learning Islamic religious education at SMA Negeri 3 Pasuruan City. This study used a quantitative approach using a sample of 140 students in class XI at SMA Negeri 3 Kota Pasuruan. The data was collected by distributing questionnaires and conducting interviews. The results of the descriptive analysis show that there is a significant influence between the Learning Model Market Place Activity or Sales Promoting Activity Creative with the interest in learning Islamic religious education. And seen from the results of inferential statistical analysis shows that the correlation test and simple linear regression test obtained results, that there is a significant influence between the Market Place Activity or Sales Promoting Activity Creative Learning model on the interest in learning Islamic education by 51.8% while the remaining 48.24% is influenced by other factors. Based on the results of descriptive analysis (qualitative in nature) it shows that the Marlet Place Activity or Sales Promoting Creative Activity learning model in SMA Negeri 3 Kota Pasuruan is in the category of very many students asking to learn Islamic Religious Education, namely feeling happy in learning, not boring, active in learning, can build freedom of expression through creativity.